2020
DOI: 10.1088/1742-6596/1550/2/022002
|View full text |Cite
|
Sign up to set email alerts
|

Design and Construction of Information-based Teaching Cloud Space in Colleges and Universities under the Framework of TPACK

Abstract: In order to improve the quality of information-based teaching in colleges and universities, promote the penetration of information technology into the classroom, and improve the teaching effect, based on the TPACK framework, this paper designs the information-based teaching cloud space in colleges and universities, and constructs the system framework by combining the learning theory and teaching needs with the characteristics of the cloud space. Teaching cloud space is to carry out research from four dimension… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 0 publications
0
6
0
Order By: Relevance
“…According to the analysis of Figure 4, this method can effectively evaluate the quality constraint parameters of college classroom activities, improve the clustering level of data and test the fusion degree of different methods in evaluating the quality constraint parameters of college classroom activities. e assessment and comparative outcomes with the [4,5], are given away in Table 2, which shows that the correctness of the suggested approach in evaluating the quality of college classroom activities is high.…”
Section: Simulation Tests and Resultsmentioning
confidence: 97%
See 2 more Smart Citations
“…According to the analysis of Figure 4, this method can effectively evaluate the quality constraint parameters of college classroom activities, improve the clustering level of data and test the fusion degree of different methods in evaluating the quality constraint parameters of college classroom activities. e assessment and comparative outcomes with the [4,5], are given away in Table 2, which shows that the correctness of the suggested approach in evaluating the quality of college classroom activities is high.…”
Section: Simulation Tests and Resultsmentioning
confidence: 97%
“…Due to the complexity, fuzziness, and multi-factors of the teaching phenomenon in the effectiveness evaluation of teaching accomplishments in colleges and academies, there is a problem with qualitative analysis and accuracy in the effectiveness evaluation of teaching undertakings. By constructing an optimized assessment model of teaching actions in colleges and academies, combining with the teaching quality evaluation of the classroom, the scientific, reasonable, and fair index parameter analysis technique are implemented to comprehend the effectiveness analysis and dynamic assessment of teaching events in colleges and academies, thus ensuring and steadily improving the teaching quality [4]. Generally, the evaluation index system for the effectiveness evaluation of classroom actions in institutions of higher learning should include two factors: (i) one is the index that can fully reflect the effectiveness and teaching quality of classroom accomplishments in institutions of higher learning; and (ii) the other is the weight of each index on the effectiveness and importance of classroom happenings in institutions of higher learning.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Teachers need to be prepared to use technology in teaching by following training (Fauzi et al, 2019;Munusamy & Nordin, 2021). Akyuz (2018); Gan et al (2020) showed that factors such as learning style, level of technology readiness, and group dynamics can affect learning outcomes in an online collaborative environment (Jamruz & Razali, 2021;Nasir, 2020;Nasir & Ngah, 2022). Apart from that, the Cakir & Korkmaz (2019) study also reported that AR activities designed for Down Syndrome students positively contributed to the increased level of students' readiness, enthusiasm, motivation, confidence, and readiness.…”
Section: Teachers' Readiness To Integrate Technology In Their Teachin...mentioning
confidence: 99%
“…The essence of improving learning delivery systems is to enhance learner's experience, promote best teaching practices and improve access (Gan et al, 2020;Mhouti et al, 2018;Ouadoud et al, 2018). Tutmas is a tool to improve management of tutorials at the University.…”
Section: Students Perception In Using Tutmasmentioning
confidence: 99%